Peran Media Sosial Dalam Penyebaran Dakwah Islam di Era Digital Perspektif Al-Qur’an - Urokhim, Auliya; Rosyida, Ela (Department of Da'wah Management, Faculty of Da'wah, IAINU Tuban, 2025)
This article discusses the role of social media in the dissemination of Islamic da'wah in the digital era, with reference to the Qur'anic perspective. In the modern context, social media has become an effective tool for delivering da'wah messages to the wider public. Through the analysis of various studies, this article shows how platforms such as Instagram, Twitter and TikTok are used by the da'wah community to reach a larger and more diverse audience. It also identifies the communication strategies applied in digital da'wah, including the use of visual and interactive content that attracts the younger generation. In addition, this article highlights the challenges faced in the dissemination of da'wah through social media, such as misinformation and different interpretations of teachings. Thus, this article aims to provide a deeper understanding of the dynamics of Islamic da'wah in the digital era and how social media can be optimally utilised to spread Islamic values in accordance with the teachings of the Qur'an.